Maturity grid to evaluate and improve environmental management in industrial companies - Campos, Thalita Láua Reis [UNESP]; da Silva, Fabio Francisco; de Oliveira, Karine Borges [UNESP]; de Oliveira, Otávio José [UNESP] (Springer Nature, 2020)
Abstract: The increase in industrial activities to meet the growing needs of the population has led many companies to adopt environmental management (EM) policies to offset their impacts on the environment. For this reason, this article proposes a tool to identify the maturity levels of the elements of EM in industrial companies. The principles and practices of these elements were identified in the scientific literature and their practice was tested in an industrial company using the proposed tool. The main results show that the proposed tool allows to measure the maturity of the EM principles in industrial companies, making it possible to direct efforts toward EM elements with lower level of maturity. Graphic abstract: [Figure not available: see fulltext.]
Keywords: Environmental management; Industrial companies; Maturity; Process improvement